PENINGKATAN SIKAP SPIRITUAL MODERAT SISWA MELALUI KANAL MEDSOS MATERI PAI DI SDN KROPAK 1 KABUPATEN PROBOLINGGO - Laila Badriyah; Imam Abd. Khaliq Qawi; Irma Diana Safitri; Abdul Kholiq; Alfiatu Maghfiroh (Journal Multicultural of Islamic Education, 2023)
This study investigates the qualitative impact of utilizing social media, specifically YouTube, for Islamic Education (PAI) at SDN Kropak 1, Probolinggo, the research employs direct observations, interviews, and descriptive analyses. Results this study Positive outcomes include increased student engagement, curiosity, and knowledge acquisition. Challenges include technical constraints and student resistance to behavioral change. High student participation, altered attitudes, enhanced material comprehension, active discussion involvement, positive feedback from parents and teachers, parental engagement, improved discipline, and successful learning assessments. The study underscores the effectiveness of social media in enhancing students' spiritual attitudes. Continuous evaluation informs future initiatives for nurturing spiritual inclinations.